Multidimensional assessment of a Nature-based Solution for decentralized greywater treatment in Costa Rica - Maria Perez Rubi; Conrad Schiffmann; Jochen Hack (Nature-Based Solutions)
In Costa Rica, water supply networks provide water to over 94% of the country's population. However, only an estimated 14% of wastewater receives proper treatment. The lack of centralized sanitation infrastructure has resulted in the use of septic tanks and the discharge of untreated greywater into rivers, causing environmental degradation of surface waters. Retrofitting conventional centralized sewer networks and treatment plants into the existing urbanization presents extensive social, economic, and technical challenges. Nature-based Solutions (NbS) for greywater treatment can reduce pollutant loads and improve the environmental status of water resources and represent an opportunity for technical leapfrogging towards sustainable, decentralized on-site treatment and reuse. However, the implementation of NbS in urban areas poses significant challenges due to the complex interplay of social, regulatory, and economic factors. Specifically, for on-site greywater treatment systems, meeting several criteria, including efficient pollutant removal, affordability, and public acceptance is essential for successful implementation and operation. This study assesses the technical, socio-economic, and political-regulatory dimensions relevant to implementing NbS for decentralized greywater treatment. To conduct this research, a Real-World Lab was established in the Great Metropolitan Area of Costa Rica, employing a transdisciplinary approach. This approach provided a physical space and societal context to integrate site-specific aspects and understand the various factors that influence the implementation and upscaling of NbS. As part of our methodology, we analyzed the water quality parameters and treatment performance of a NbS prototype for decentralized greywater treatment. Within the Real-World Lab framework, we conducted interviews, surveys, and field observations to investigate socio-economic and political-regulatory aspects. Our results highlight the technical potential of the NbS prototype. However, the limitation lies in the governance scheme and financing mechanisms required for upscaling the NbS as a decentralized on-site technology across the country. Our multidimensional assessment provides insights into the requirements for widespread implementation of NbS, applicable to other regions facing similar retrofitting sanitation challenges.